Homeroom Leadership Style in the Learning Process - Alif Rizal Fauzi, Achmad; Tinda Kusuma, Edwin; Wijayanto, Anang; Catur Wahyuni, Hana; Fariyatul, Eni; Maharani, Okvi (Annpublisher, 2023)
Leaders are in charge of determining where an organization will run. The leader is a sign,model, mover, and source of influence, who can control various activities and resources to achievehis goals. Leadership will produce a conducive work culture by encouraging member performancestrategies to increase the work motivation of all organization members. This research aims to look atthe homeroom teacher's leadership style in the learning process in grade 1 elementary school. Themethod used in this study is a qualitative method with descriptive analysis techniques. The result ofthis study is that the leadership style applied to grade 1 SD Antawirya is the modern leadership styleof the boarding. This is considered from the concept of the Antawirya Elementary School, whichadopts the boarding culture but does not forget the values of character development such as openness,flexibility, and good morals. However, the authors do not yet know how the influence of the modernleadership style of the boarding on student achievement. Therefore, the authors suggest that futureresearchers can further examine the influence of modern leadership by the homeroom teacher of SDAntawirya on student achievement.